The impact of personal tax rate reduction on purchasing power and economic stability - Iskandar, Arif Haikal; Azis, Saflina; Mat, Mustafa Kamal (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Fiscal management in Malaysia focuses on managing national financial resources to promote economic growth, improve public services, and support effective policymaking. Personal income tax policy plays a key role in this process, as reducing tax rates can increase disposable income, stimulate consumption, and encourage investment. During economic slowdowns, including regional recessions and the COVID-19 pandemic, tax cuts have been considered to generate multiplier effects that boost production and employment. However, while increased household spending can sustain economic expansion, policymakers must carefully balance growth objectives with potential revenue shortfalls and fiscal deficits.